Ecosystem-specific advantages in international digital commerce - Li, Jiatao; Chen, Liang; Yi, Jingtao; Mao, Jiye; Liao, Jianwen (Journal of International Business Studies, 2019)
We consider the applicability to digital platforms of extant international business scholarship. The organization of digital platforms has been seen to such an extent as predicated upon the bundling of external resources for collective value creation that their expansion may follow the logic of externalization. We further that literature contrasting the governance of network multinationals with that of platform-centric ecosystems. Building on and extending the theory of the ecosystem, we propose the concept of ecosystem-specific advantages. We identify costs and difficulties in the transfer of such advantages to new markets, emphasizing in particular the idea of bottlenecks. We then propose a framework that can be applied to future research on digital platforms, focusing on the users, suppliers of complementary products, and platform firms. We also call for research on the dynamic process of creating, transferring, and upgrading ecosystem-specific advantages.